THE OBJECTIVES OF SHARIA (MAQASID AL-SHARI'A) AND THEIR CLASSIFICATION (The Journal of Interdisciplinary Human Studies, 2026)
This academic article analyzes the objectives of Sharia namely, the theory of maqaṣid al-shariʿa focusing on its formation, development, fundamental principles, and contemporary applications. The study is based on the conceptual frameworks developed by major scholars such as Imam al-Ghazali, Imam al-Shatibi, and Ibn ʿAshur
Keywords: maqaṣid al-shariʿa; necessities; needs; refinements; maṣlaḥa; ijtihad